2002
DOI: 10.1073/pnas.112194599
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic gene nested within an intron of the tau gene: Implications for Alzheimer's disease

Abstract: A previously undescribed gene, Saitohin (STH), has been discovered in the intron between exons 9 and 10 of the human tau gene. STH is an intronless gene that encodes a 128-aa protein with no clear homologs. The tissue expression of STH is similar to tau, a gene that is implicated in many neurodegenerative disorders. In humans, a single nucleotide polymorphism that results in an amino acid change (Q7R) has been identified in STH and was used in a case control study. The Q7R polymorphism appears to be over-repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(134 citation statements)
references
References 24 publications
7
124
3
Order By: Relevance
“…15 There is immunohistochemical evidence that STH produces a protein product, 15 but studies have demonstrated that STH may be involved in the regulation of 3R and 4R MAPT splicing. 36,37 In the current study, it was found that higher expression of STH was strongly correlated with higher expression of both 3R and 4R MAPT isoforms across all samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 There is immunohistochemical evidence that STH produces a protein product, 15 but studies have demonstrated that STH may be involved in the regulation of 3R and 4R MAPT splicing. 36,37 In the current study, it was found that higher expression of STH was strongly correlated with higher expression of both 3R and 4R MAPT isoforms across all samples.…”
Section: Discussionmentioning
confidence: 99%
“…STH, a single-exon gene located within intron 9 of MAPT, has shown similar tissue distribution to MAPT, suggesting that the two genes may be co-regulated in certain tissue types. 15 The finding of modest evidence for linkage to PD affection in the GenePD Study (nonparametric lod score = 1.7 on chromosome 17 at 63.8-63.9 cM) justified an examination of the MAPT region. We analyzed the association of 21 SNPs spanning MAPT, STH, and KIAA1267 to PD in the GenePD Study.…”
mentioning
confidence: 99%
“…The complexity of gene expression includes alternative splicing mechanisms, 1 alternative promoter-enhancer usage, 2 intronic gene expression, 3 expression of inhibiting RNAs, 4 and effects of DNA polymorphisms. 5 Such mechanisms likely account for the large diversity of proteins (greater than 100 000 per cell) derived from a relatively small number of human genes (around 30 000) and for their expression with tissue and developmental specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the H1 haplotype was further expanded to include the promoter region of MAPT and now spans a region of ~1.8Mb in complete linkage disequilibrium (de Silva et al, 2001;Pittman et al, 2004). This extended haplotype contains several genes in addition to MAPT, including CRHR1 (corticotrophin-releasing hormone receptor 1), NSF (Nethylmaleimide sensitive factor), IMP5 (intramembrane protease 5), WNT3 and STH (saitohin), a gene nested in the intron 9 of MAPT (Conrad et al, 2002;Pittman et al, 2004). A ~900kb segment of the H2 haplotype including MAPT has been found to be inverted in respect to H1.…”
Section: Tau As a Genetic Risk Factor For Neurodegenerative Diseasesmentioning
confidence: 99%